Experimental characterisation of the screech feedback loop in underexpanded round jets. (5th July 2017) - Mercier, Bertrand; Castelain, Thomas; Bailly, Christophe
Abstract : Near-field acoustic measurements and time-resolved schlieren visualisations are performed on 10 round jets with the aim of analysing the different parts of the feedback loop related to the screech phenomenon in a systematic fashion. The ideally expanded Mach number of the studied jets ranges from $M_{j}=1.07$ to $M_{j}=1.50$ . The single source of screech acoustic waves is found at the fourth shock tip for A1 and A2 modes, and at either the third or the fourth shock tip for the B mode, depending on the Mach number. The phase of the screech cycle is measured throughout schlieren visualisations in the shear layer from the nozzle to the source. Estimates of the convective velocities are deduced for each case, and a trend for the convective velocity to grow with the axial distance is pointed out. These results are used together with source localisation deduced from a two-microphone survey to determine the number of screech periods contained in a screech loop. For the A1 and B modes, four periods are contained in a loop for cases in which the radiating shock is the fourth, and three periods when the radiating shock tip is the third, whereas the loop of the A2 mode contains five periods.